IMPLEMENTASI SCAN MARKER AUGMENTED REALITY UNTUK MEDIA PENGENALAN ORGAN TUBUH MANUSIA - Rifai, Anes Sayful Bahtiyar; Aji, Adam Sekti (Politeknik Bisnis Indonesia, 2023)
Learning involves the exchange of information and knowledge between educators, disciples, and educational resources. Currently, the transmission of educational content from educators to disciples generally has not used technology as a learning tool, thus making disciples exhibit a lack of enthusiasm and experience disinterest when it comes to grasping educational content. Researchers designed and created an application as an interactive learning tool to learn human organs for elementary school students. The research findings are translated into an application for the introduction of human organs using Augmented reality technology, all button functions on the hull learning application function properly. The accuracy of marker detection is influenced by several parameters including light intensity, marker scanning distance, and marker movement. This learning application's aim is to facilitate the learning application of human organs for elementary school students fun and easy to learn by elementary school students, successfully achieved.